Políticas de formação em psicologia em Goiás: diretrizes curriculares e projetos pedagógicos - Campos, Maurício (2014)
The central focus of this research study were the Political Training in Psychology in Goiás, surveyed from the curricular and pedagogical projects matrices Course (PPC). These policies were problematized from the relationship with the educational policies for higher education, approved in the decades of 1990 and 2000. In this historical context, we sought to situate the pendulum between the minimum curriculum for training in psychology, approved in 1962, debates in the field and propose the National Curriculum Guidelines (DCNs) that were approved in 2004 and revised in 2011, which translates disputes between different actors. The study is located in the first psychology course of Goiás was created in 1973 at the Pontifical Catholic University of Goiás (PUC -GO). How expansionary dynamic , points out that only in 2000 was created a second course in Goiás , through the Universidad Paulista (UNIP), and later, in 2006, implanted the psychology course in a free public institution in the University Federal de Goiás ( UFG ) Campus in Goiania . In the first decade of this century, there was an expansion of courses in Psychology in the state in 2001, had two strokes and that number in 2012, fourteen. These indicators show that training policies in Psychology in Goias accompanied the expansionist logic that occurred in higher education at the beginning of the century, marked by the diversification and differentiation and predominantly private logic. These courses, only three courses are offered in public institutions and the remaining (eleven courses) in private institutions. Considering this scenario, we performed the following procedures for data collection: literature review, desk research and interviews. Aiming to cut the theme , emphasizing the educational process , curriculum matrices of fourteen courses were analyzed and PPC courses offered on - campus UFG Goiânia , UFG - Campus Catalan , UFG - Campus Jatai and PUC -GO . Six interviews, three with course coordinators and three faculty members of the Core Faculty Structuring (NDE) were performed. The collected data were analyzed by means of document analysis and content analysis. It found little organicity in the construction of training policies and the dominance of technical aspects in the matrices. On the other hand, and concomitantly, paradoxically, became evident advances in training proposal, such as the expansion of theoretical epistemes and areas despite the maintenance aspects / disciplines to at least resume. Evidenced through the constação, for example, the similarity between the curriculums fourteen arrays analyzed, indicating possible crystallization of these training. The study, by locating goiano case, refers to national policies and the necessary contextualization of these. The Goias case is important to the extent that it reveals the unfolding of DCNs on PPC and Pedagogical Projects Course. Thus indicating correlations, limits and specificities. The study also highlights the need for further research to advance the understanding of such policies and thereby uncover new ideas and propositions on training in psychology and its contextualization, especially in social change -oriented perspective in spite limits and structural and economic constraints.